Development of a self-regulated bubble irrigation system to control the size and shape of wetting fronts - Alrubaye, Yasir Layth; Yusuf, Badronnisa; Hamad, Safaa Noori (Universiti Putra Malaysia Press, 2020)
The main objectives of this study were to introduce a bubble irrigation system, compare the wetting fronts created by the bubble and free-flow systems, and test the viability of a bubble irrigation system. Two laboratory experiments were conducted using 2D flow to measure the wetting fronts. The first experiment measured the free-flow infiltration using an inverted, open plastic bottle. The second experiment tested the bubble-flow technique using an inverted, closed plastic bottle (ICPB). The results showed that the bubble-flow system created a larger width of wetting fronts at the beginning of the infiltration and then expanded less than that of the free-flow system. In contrast, the infiltration depth of the wetting fronts created by the bubble-flow system was much lower than that of the free-flow system. In conclusion, the wetting front width and depth in the bubble-flow system were slightly smaller than those in the free-flow system. In addition, the wetting fronts created by the ICPB were not moved upwards significantly, which proves the ability of specific distribution of the bubble-flow system on the wetting fronts. Therefore, the bubble irrigation system can be used as an alternative for distributing the moisture content in soil profiles.